Tooth Agenesis in A Seven Year Old Child at RSGM Soelastri Surakarta Case Report - Devina Pramesti Intan Faradilla; Septriyani Kaswindiarti (Universitas Duta Bangsa Surakarta, 2026)
Agenesis is a dental anomaly that occurs relatively frequently in humans. Agenesis results in the failure of teeth to develop after birth, with tooth development occurring only during childhood. The prevalence of permanent dental agenesis in non-syndromic individuals is higher among Europeans, with 4.6% in males and 5.5% in females, in Australia 5.5% in males and 7.6% in females, and lower among Caucasian Americans, with 3.2% in males and 4.6% in females. A 7-year-old male patient came to RSGM Soelastri with his mother, complaining of small and sharp teeth. In the intraoral examination, abnormalities were found in the deciduous teeth, showing hypodontia where the tooth bud of 42 did not develop. Beside of hypodontia, this case also exhibited a peg shape in tooth 82. The patient's parents should be given communication, information and education regarding the issues that occur. The diagnosis of agenesis requires clinical and supportive examinations. It can be concluded that the main factor causing agenesis and peg shape is genetic.